Assessing the effectiveness of reduced parking requirements in facilitating transit-oriented development: a case study of “PT areas” in Cape Town - Sasman, Nicola Anne (Department of Civil Engineering, 2023)
There has been a paradigm shift in thinking about parking provision, as government policy has favoured public transport and non-motorised transport (NMT), to limit and manage its supply in cities. This has been informed by sustainability principles, the understanding of “transit-oriented development” (TOD), and the “triple access” system thinking. This thinking has been applied in various ways in different cities, and its application in the literature is explored here, including case study lessons. This dissertation aims to answer the question: Recognising the current car-centric nature of the modern city (both in the Global North and South) on the one hand, and the sustainability and social equity imperatives on the other, can reduced parking provision and improved parking management be used to support the restructuring of the city over time, in support of public transport and of transit-oriented development? Cape Town is used as a case study, by assessing the effectiveness of the implementation of a tool adopted by the City of Cape Town, called “public transport areas” (“PT areas”), which allows reduced off-street parking supply in centres which are well-served by public transport. The research quantifies the number of parking bays not supplied as a result of the uptake of this PT offering, and locates this geographically. This was undertaken in 2 phases: the municipality conducted a pilot study of a small sample of centres, led by the author. The lessons learnt from this then informed the methodology for the full analysis, with the City providing the data to the author for analysis in her capacity as a student. The results of the quantitative research show that there was a significant nett saving of 9 662 parking bays in all centres, resulting in the freeing up of at least 18ha of developable land for more productive use. This does not include the additional gross lettable area potential created by reduced parking requirements, specific to each erf and land use. The research concludes that a tool such as the “PT offering” can have an impact on land use intensification, but its effectiveness is dampened if a good public transport system is not in place to enable positive travel behaviour change. It recommends that the moment is right, due to changing behaviour as a result of the COVID-19 pandemic, for authorities to take actions to reduce parking demand and supply, and related management, in support of more people- and planet-orientated cities.civil